Urban food prices under lockdown: Evidence from Myanmar’s traditional food retail sector during COVID-19 - Goeb, Joseph; Maredia, Mywish K.; Win, Khin Zin; Masias, Ian; Lambrecht, Isabel B.; Boughton, Duncan; Minten, Bart (International Food Policy Research Institute, 2021)
Many governments imposed stringent lockdowns during the COVID-19 pandemic as a public health measure to suppress the spread of the disease. With consumer incomes already depressed, the potential impacts of these measures on urban food prices are of particular concern. This working paper examines the changes in Myanmar’s urban food prices during lockdown using detailed food price data collected from a panel of phone surveys conducted in August and September 2020 of 431 family-owned retail shops in Myanmar’s two largest cities, Yangon and Mandalay. We find that the supply side of Myanmar’s food retail sector was largely resilient to the shocks and lockdowns throughout the first six months of the COVID-19 pandemic. Estimates from a fixed effects differencein-differences model reveal that food prices were 3 percent higher in townships under lockdown compared to those not under lockdown, a statistically significant but modest effect. Lockdowns had smaller effects on prices for highly processed food items sourced directly from companies, but larger effects on prices for raw or lightly processed commodities sourced through wholesale markets, which comprise a larger share of urban consumer’s diets. Retailer margins did not change significantly under lockdown restrictions, suggesting no evidence of price gouging. Overall, our findings of a modest impact of the lockdown on urban food prices underscore the importance of keeping the food supply chain–including wholesale markets and retail shops–functioning as completely and as safely as possible during times of crisis, as was mostly the case early in the crisis for the two cities in this study.